Federal Rules of Bankruptcy Procedure - Cromar, Scott A.; Lawless, Robert M. (Open textbook library., 2014)
The Federal Rules of Bankruptcy Procedure appear in the Appendix to Title 11 of the United State Code. This publication was made with data provided by the United States government on the Office of Law Revision Counsel Bulk US Code. This title is current through July 31, 2014.